Dampak Kecemasan Matematika terhadap Hasil Belajar Siswa: Study Literatur Review - Dwi Nazwa Adisti; Hasanuddin Hasanuddin (Jurnal Wahana Literasi Pendidikan, 2026)
This article was written using a literature study method focusing on the impact of students’ mathematics anxiety on their learning outcomes. Mathematics anxiety is one of the factors that can affect students’ learning outcomes. The analysis resulted in an understanding of anxiety and mathematics anxiety, the factors causing mathematics anxiety, and efforts to overcome students’ mathematics anxiety. Anxiety is an emotional process that occurs when a person experiences worry and uneasiness, resulting in emotional distress. Mathematics anxiety refers to feelings that arise when a person is confronted with situations related to mathematics, whether during the learning process, mathematics tests, or in everyday life involving mathematical calculations. Three factors influence mathematics anxiety: personality factors, intellectual factors, and environmental factors. Efforts that students can undertake to reduce the mathematics anxiety they experience include reducing negative thoughts about mathematics, developing confidence in their own abilities, and creating a relaxed and calm learning environment.